ANALYZING SUBSTITUTABILITY IN THE WORLD MARKET OF VEGETABLE OILS FROM THE PRICE TRANSMISSION - de Castro, Lucas Siqueira (Contextus - Revista Contemporânea de Economia e Gestão, 2016)
This study analyzed the elasticity of price transmission in the soybean oil market for palm oil, sunflower and canola from October 1997 to September 2016. From the concepts of the theories of the relevant market and market integration, it were estimated an error-correction models (VEC) for palm, sunflower and canola oils. The results showed that in the long term, the markets palm, sunflower and colza oils are integrated with that of soybean oil, thus being substitutes. The impulse response functions indicated that unanticipated changes in soybean oil prices are not dissipated for other vegetable oils. The decomposition of the variance of the palm, sunflower and canola oils showed that in the last analyzed month, soybean oil accounted for 62.36%, 55.12% and 44.76% of their prices.